The red/blue light ratios from light-emitting diodes affect growth and flower quality of Hippeastrum hybridum ‘Red Lion’ - Wang, Shunli; Liu, Xiaoting; Liu, Xiaoning; Xue, Jingqi; Ren, Xiuxia; Zhai, Yanning; Zhang, Xiuxin (Frontiers in Plant Science, 2022)
Light quality strongly impacts the growth and flower quality of ornamental plants. The optimum light quality for the growth and flowering of Hippeastrum remains to be validated. In the present study, we investigated the effect of the red/blue light ratio of LEDs on the growth and flowering quality of H. hybrid ‘Red Lion’. Two LEDs with red/blue light ratio of 1:9 (R10B90) and 9:1 (R90B10) were designed. LEDs of white light were the control. In the earlier vegetative and reproductive growth phase, R90B10 increased the biomass of the bulbs, leaves, and flowers. Compared with the control and R10B90 group, R90B10 LEDs delayed flowering by 2.30 d and 3.26 d, respectively. Based on chlorophyll contents, photosynthetic capacity, chlorophyll fluorescence parameters, and carbohydrate contents, the photosynthesis rate was higher in the R10B90 group. Optimal red and blue light intensity promoted the accumulation of carbohydrates and early flowering and prolonged the flowering period of H. hybrid. Microscopic analysis showed that stomatal density was high, and the number of chloroplasts was large in the R10B90 treatment group, which enhanced photosynthesis. Particularly, R10B90 promoted the expression of seven key genes related to chlorophyll synthesis. R10B90 also promoted early overexpression of the HpCOL gene that promotes early flowering. Thus, higher blue light and 10% red light intensities promote early and extended flowering, while higher red light and 10% blue light promote vegetative plant growth but delay flowering.